2009
DOI: 10.5551/jat.992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pitavastatin on Serum Lipids and High Sensitivity C-Reactive Protein in Type 2 Diabetic Patients

Abstract: Aim: Previous studies have been inconsistent results about the effects of statins on serum triglyceride (TG), high-density lipoprotein cholesterol (HDL-C) and high sensitivity C-reactive protein (hsCRP) levels. We therefore investigated the effects of pitavastatin on serum lipid profiles and hsCRP levels in patients with type 2 diabetes mellitus. Methods: The study population was 65 Japanese type 2 diabetic patients who had been administered 2 mg daily of pitavastatin and completed a 6-month follow-up. Serum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…Furthermore, pitavastatin is generally associated with a greater HDL-C elevating efficacy than atorvastatin, simvastatin or pravastatin that is consistently increased over the long term [Hounslow et al 2010;Ose et al 2010Ose et al , 2009Watson, 2010;Budinski et al 2009;Teramoto et al 2009Teramoto et al , 2007Stender and Hounslow, 2009;Kurihara et al 2008;Yokote and Saito, 2008]. In addition to pitavastatin's potent effects on lipid profiles, a number of pleiotropic benefits have been identified that may contribute to a reduction in residual CV risk in people with dyslipidaemia and could partly account for pitavastatin's ability to regress coronary plaques in patients with ACS [Egashira, 2009;Hiro et al 2009;Motomura et al 2009;Nakano and Ohbayashi et al 2009;Koshiyama et al 2008;Inoue et al 2007;Sagara et al 2007;Kawakami et al 2005;Kibayashi et al 2005;Han et al 2004;Hiraoka et al 2004;Morikawa et al 2004Morikawa et al , 2002Hiraoka and Yoshida, 2003;Markle et al 2003;Suzuki et al 2003]. Importantly, the safety and tolerability profiles of pitavastatin 14 mg are similar to those of atorvastatin, pravastatin, and simvastatin at doses with comparable efficacy (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, pitavastatin is generally associated with a greater HDL-C elevating efficacy than atorvastatin, simvastatin or pravastatin that is consistently increased over the long term [Hounslow et al 2010;Ose et al 2010Ose et al , 2009Watson, 2010;Budinski et al 2009;Teramoto et al 2009Teramoto et al , 2007Stender and Hounslow, 2009;Kurihara et al 2008;Yokote and Saito, 2008]. In addition to pitavastatin's potent effects on lipid profiles, a number of pleiotropic benefits have been identified that may contribute to a reduction in residual CV risk in people with dyslipidaemia and could partly account for pitavastatin's ability to regress coronary plaques in patients with ACS [Egashira, 2009;Hiro et al 2009;Motomura et al 2009;Nakano and Ohbayashi et al 2009;Koshiyama et al 2008;Inoue et al 2007;Sagara et al 2007;Kawakami et al 2005;Kibayashi et al 2005;Han et al 2004;Hiraoka et al 2004;Morikawa et al 2004Morikawa et al , 2002Hiraoka and Yoshida, 2003;Markle et al 2003;Suzuki et al 2003]. Importantly, the safety and tolerability profiles of pitavastatin 14 mg are similar to those of atorvastatin, pravastatin, and simvastatin at doses with comparable efficacy (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improving lipid profiles, pitavastatin significantly reduced serum CRP levels by 34.8% versus baseline (p < 0.01). Although there have been conflicting results on the efficacy of other statins on CRP-lowering in patients with diabetes [Economides et al 2004;Sommeijer et al 2004;Tan et al 2002], the KISHIMEN study [Koshiyama et al 2008] and a more recent study by Motomura and colleagues [Motomura et al 2009] showed that pitavastatin has a significant CRP-lowering effect in people with type II diabetes that is not related to reductions in lipid profile. Although the effects of pitavastatinmediated CRP lowering on CV morbidity and/or mortality have not yet been studied in clinical trials, a number of studies have shown that CRP reduction using other statins is associated with significant reductions in CV endpoints [Ridker et al , 2005de Lemos et al 2004].…”
Section: Effects Of Pitavastatin On Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some differences between study results do exist as noted above. showed significant reductions in TC (P<0.LDL ≥120 mg/dL and TG <400 mg/dL) 60. Significant reductions in hs-CRP were also seen after 6 months of pitavastatin therapy as compared with baseline (P<0.05).…”
mentioning
confidence: 59%
“…We have previously reported that pitavastatin significantly reduced serum levels of LDL-C, remnant-like particle cholesterol (RLP-C), and hs-CRP, and raised HDL-C levels in a multi-center, prospective, open-label study, namely the Kansai Investigation of Statin for Hyperlipidemic Intervention in Metabolism and Endocrinology (KISHIMEN) 14) . Subsequently, another group demonstrated similar results using pitavastatin 21) . In this study, we sought to determine whether pitavastatin also lowers serum levels of IL-18, another inflammatory biomarker, in the same serum samples derived from the KISHIMEN study, in which hs-CRP levels were measured 14) .…”
Section: Introductionmentioning
confidence: 67%